2018
DOI: 10.1038/s41598-018-27899-9
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Mcl-1 inhibitors from integrated high throughput and virtual screening

Abstract: Protein-protein interactions (PPIs) represent important and promising therapeutic targets that are associated with the regulation of various molecular pathways, particularly in cancer. Although they were once considered “undruggable,” the recent advances in screening strategies, structure-based design, and elucidating the nature of hot spots on PPI interfaces, have led to the discovery and development of successful small-molecule inhibitors. In this report, we are describing an integrated high-throughput and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 78 publications
2
15
0
Order By: Relevance
“…Moreover, the NMR data suggested an interaction with Gly219, Val220 and Val216, part of the P4 pocket, for both ligands. This observation was also highlighted from similar NMR data reported by Mady et al, 68 for a set of Mcl-1 inhibitors. These interactions at the P4 pocket might rise from a non-direct effect due to the presence of aromatic rings (ring-current effect) as we have previously discussed for Pyridoclax 36 for instance.…”
Section: Resultssupporting
confidence: 82%
“…Moreover, the NMR data suggested an interaction with Gly219, Val220 and Val216, part of the P4 pocket, for both ligands. This observation was also highlighted from similar NMR data reported by Mady et al, 68 for a set of Mcl-1 inhibitors. These interactions at the P4 pocket might rise from a non-direct effect due to the presence of aromatic rings (ring-current effect) as we have previously discussed for Pyridoclax 36 for instance.…”
Section: Resultssupporting
confidence: 82%
“…[44][45][46] Importantly, there is a conserved arginine residue on pro-life proteins (Arg263 in Mcl-1) that forms a salt bridge with Asp67 on the Bim α-helix at the i + 5 position. [47] Additionally, there is an aspartate residue in an analogous location (i + 2) in p53TAD (Asp21), that helps maintain the integrity of the helix rather than engage in recognition. [48] We set out to capitalize on these similarities across both α-helices towards the discovery of dual inhibitors of Mcl-1 and HDM2.…”
Section: Resultsmentioning
confidence: 99%
“…Aside from the on-target toxicity concerns, Bcl-xL remains an important therapeutic target, especially in solid tumors, therefore development of selective Bcl-xL inhibitors remains an attractive approach. , The selective Bcl-2 inhibitor, ABT-199 or venetoclax, is the first BH3 mimetic with granted FDA approval for its success in treating chronic lymphocytic leukemia and is currently being evaluated in numerous clinical trials for various indications. , The need for selective Mcl-1 inhibitors emerged from the observance of Mcl-1 as a prominent resistance factor to other BH3 mimetics, as well as to many targeted chemo- and radiotherapies . This need was addressed by selective Mcl-1 inhibitors developed by our group and others, both in academia and industry. The work on selective Mcl-1 inhibitors has culminated to several compounds now being evaluated in phase I clinical trials for the treatment of hematologic malignancies as a single agent (ClinicalTrials.gov; NCT02675452, NCT03465540, NCT02979366, NCT02992483, NCT03218683) and in combination with venetoclax (ClinicalTrials.gov; NCT03672695). There is still a need, however, to effectively target Bfl-1 with drug-like molecules, as the main successes have come from selective peptides. We and others, using biochemical screening assays, have identified hit small molecule inhibitors of Bfl-1 which require further optimization. , A recent study identified bicyclic stapled peptides as dual Mcl-1/Bfl-1 inhibitors with cellular activity and demonstrated an opportunity to develop Noxa-mimetic type inhibitors …”
Section: Introductionmentioning
confidence: 99%
“…This need was addressed by selective Mcl-1 inhibitors developed by our group and others, both in academia and industry. The work on selective Mcl-1 inhibitors has culminated to several compounds now being evaluated in phase I clinical trials for the treatment of hematologic malignancies as a single agent (ClinicalTrials.gov; NCT02675452, NCT03465540, NCT02979366, NCT02992483, NCT03218683) and in combination with venetoclax (ClinicalTrials.gov; NCT03672695). There is still a need, however, to effectively target Bfl-1 with drug-like molecules, as the main successes have come from selective peptides. We and others, using biochemical screening assays, have identified hit small molecule inhibitors of Bfl-1 which require further optimization. , A recent study identified bicyclic stapled peptides as dual Mcl-1/Bfl-1 inhibitors with cellular activity and demonstrated an opportunity to develop Noxa-mimetic type inhibitors …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation